2018
DOI: 10.3389/fimmu.2018.01721
|View full text |Cite
|
Sign up to set email alerts
|

Secreted Phospholipases A2 in Hereditary Angioedema With C1-Inhibitor Deficiency

Abstract: BackgroundHereditary angioedema (HAE) caused by deficiency (type I) or dysfunction (type II) of the C1 inhibitor protein (C1-INH-HAE) is a disabling, potentially fatal condition characterized by recurrent episodes of swelling. We have recently found that patients with C1-INH-HAE have increased plasma levels of vascular endothelial growth factors and angiopoietins (Angs), which have been associated with vascular permeability in several diseases. Among these and other factors, blood endothelial cells and vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 67 publications
1
32
0
Order By: Relevance
“…At the end of incubation, cells were centrifuged (1000× g , 4 °C, 5 min) and the supernatants were stored at −80 °C for subsequent assay of mediator release. VEGF-A and VEGF-C were measured in duplicate determinations using ELISA kits (R&D System, Minneapolis, MN, USA [ 90 ]. The ELISA sensitivity is 31.1–2000 pg/mL for VEGF-A and 62–4000 pg/mL for VEGF-C.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of incubation, cells were centrifuged (1000× g , 4 °C, 5 min) and the supernatants were stored at −80 °C for subsequent assay of mediator release. VEGF-A and VEGF-C were measured in duplicate determinations using ELISA kits (R&D System, Minneapolis, MN, USA [ 90 ]. The ELISA sensitivity is 31.1–2000 pg/mL for VEGF-A and 62–4000 pg/mL for VEGF-C.…”
Section: Methodsmentioning
confidence: 99%
“…J Investig Allergol Clin Immunol 2021; Vol. 31 (5) © 2020 Esmon Publicidad doi: 10.18176/jiaci.0524 NVC NVC (VideoCap® 3.0-D1, DS Medica, Milan, Italy) is a highly sensitive, inexpensive, simple, safe, and noninvasive imaging technique used in the morphological analysis of nourishing capillaries in the nailfold area [8].…”
Section: Introductionmentioning
confidence: 99%
“…sPLA 2 modulates vascular permeability [ 55 ] and promotes inflammation [ 52 , 53 , 56 ]. Circulating sPLA 2 levels increase the risk of early atherosclerosis [ 62 ] and predict long-term mortality of HF after myocardial infarction [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…PLA 2 activity was found increased in plasma from both groups of HF patients compared to healthy controls. PLA 2 modulates endothelial cell migration and vascular permeability in vitro and in humans [ 53 , 55 , 56 , 57 , 81 ]. Previous studies have demonstrated that circulating levels of sPLA 2 predict coronary events in patients with coronary artery disease [ 58 ], as well as in apparently healthy men and women [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation